2017
DOI: 10.1515/pjst-2017-0007
|View full text |Cite
|
Sign up to set email alerts
|

Hatha Yoga as a Form of Physical Activity in the Context of Lifestyle Disease Prevention

Małgorzata Grabara

Abstract: Physical activity is interrelated with health, physical fitness, and quality of life. The role physical activity plays in the context of lifestyle disease prevention is indisputable. Physical exercises of yoga (hatha yoga) are a type of recreational physical activity classified as a form of body and mind fitness. Hatha yoga training consists of slow or fast and smooth entering into, holding, and exiting yoga postures called "asanas". Besides asanas, a yoga class may also include breathing exercises (pranayama)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 39 publications
0
4
0
Order By: Relevance
“…On the other hand, in addition to designing programs that help increase PA at home, stress generated during the confinement situation can be managed with properly directed mental relaxation/meditation activities, with methods used even in therapies against stress and anxiety. In this sense, regular practice of activities that combine physical activity with relaxation, such as yoga, has shown multiple health benefits [50]. In this work, it was found that mental relaxation leads to significant improvements, even in short periods of time, so its use as a tool to fight the effects of the coronavirus can be promoted.…”
Section: Discussionmentioning
confidence: 97%
“…On the other hand, in addition to designing programs that help increase PA at home, stress generated during the confinement situation can be managed with properly directed mental relaxation/meditation activities, with methods used even in therapies against stress and anxiety. In this sense, regular practice of activities that combine physical activity with relaxation, such as yoga, has shown multiple health benefits [50]. In this work, it was found that mental relaxation leads to significant improvements, even in short periods of time, so its use as a tool to fight the effects of the coronavirus can be promoted.…”
Section: Discussionmentioning
confidence: 97%
“…The 2003 examination was performed with equipment designed for computer-aided evaluation of body posture and using the projection Moiré phenomenon, now commonly employed in screening diagnostics [ 31 , 32 ], and facilitating accurate and reliable quantitative assessment of numerous parameters, both in sagittal and frontal plane [ 33 ]. To ensure appropriate accuracy, the examinations were conducted in conformity with generally accepted standards [ 15 , 17 , 18 , 31 – 36 ]. It was possible to obtain a 3-dimensional image by displaying lines with specific parameters on a child’s back.…”
Section: Methodsmentioning
confidence: 99%
“…It has been established that the shape of the spine in the sagittal plane is associated with stages of ontogenetic development [ 12 ], physical fitness [ 13 ], type of physical activity [ 14 – 17 ], body weight [ 18 ], possible overloading [ 19 ] and body positioning [ 20 ]. Changes in the shape of one section of the spine tend to entail changes in the ones adjacent to or remote from the location of the original change [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The lack of physical activity is one of the symptoms of faster ageing and the cause of health loss and numerous diseases of affluence, including osteoporosis. Therefore, the prevention of osteoporosis should start at an early age and be aimed at reaching the highest possible peak bone mass, and it should be continued throughout the life span [14][15][16].…”
Section: Discussionmentioning
confidence: 99%